The Impact of High Stakes Standardized Testing on High and Low Achieving School Districts: The Case of the MCAS. - Havdala, Robert J. (Tufts Archival Research Center, 2005)
Ever since the passage of No Child Left Behind in 2002, high stakes testing has been at the forefront of the national education reform debate. Though these reforms are frequently meant to identify and help underperforming schools, there may be unintended effects on high performing districts. Previous research on high stakes testing and high performing students has yielded mixed results. This study examines the impact of the Massachusetts high stakes testing scheme (MCAS) by analyzing high school dropout rates, future plans of high school seniors, and SAT results. I find slight evidence that the gap between high and low achieving school districts has widened and note that Massachusetts students have not been affected compared to national trends. I conclude that high stakes accountability seems to have had an insignificant, if not relatively negative, impact on low achieving district performance.